The effectiveness of promotional tools practiced by One Two Three Communication (M) Sdn. Bhd. / Ikmal Hisyam Lokman Hakim - Lokman Hakim, Ikmal Hisyam (Faculty of Business and Management, 2009)
The research of "The Effectiveness of Promotional Tools Practiced by One Two Three Communications" was conducted with four objectives which are first to determine the current level of the effectiveness of promotional tools done by One two Three Communications, second to identify the most effective promotional tools towards Celcom's product are offered by One Two Three Communications, third to study the relationship between respondents profile with the total overall effectiveness and fourth to provide recommendation that can help One Two Three communications to enhance their effectiveness of promotional tools. The researcher had used Simple Random Sampling as the sampling technique. In this study, descriptive statistics had been used to interpret the data such as reliability testing, frequency tables. From the finding the respondents agree with the effectiveness of promotional tools which are advertising, sales promotions, public relations and personal selling practiced by One Two Three Communications. While the most effective promotional tools that One Two Three Communications should implement is sales promotions. The results also show the relationship between promotional tools with total overall effectiveness. Most of promotional tools used by One Two Three Communications have a positive, significance and strong relationship with the promotional tools effectiveness significant with the 0.000 at <0.05 level. Other than that the researcher also shows the relationship with between respondents' profile with the total overall effectiveness. The researcher also gave some recommendations for One Two Three Communication (M) Sdn. Bhd. to improve their promotional efforts to become more effective.